A decade of boreal rich fen greenhouse gas fluxes in response to natural and experimental water table variability - Olefeldt, David; Euskirchen, Eugénie S.; Harden, Jennifer; Kane, Evan; McGuire, A. David; Waldrop, Mark P.; Turetsky, Merritt R. (Global change biology, 2017)
Rich fens are common boreal ecosystems with distinct hydrology, biogeochemistry and ecology that influence their carbon (C) balance. We present growing season soil chamber methane emission (FCH4), ecosystem respiration (ER), net ecosystem exchange (NEE) and gross primary production (GPP) fluxes from a 9‐years water table manipulation experiment in an Alaskan rich fen. The study included major flood and drought years, where wetting and drying treatments further modified the severity of droughts. Results support previous findings from peatlands that drought causes reduced magnitude of growing season FCH4, GPP and NEE, thus reducing or reversing their C sink function. Experimentally exacerbated droughts further reduced the capacity for the fen to act as a C sink by causing shifts in vegetation and thus reducing magnitude of maximum growing season GPP in subsequent flood years by ~15% compared to control plots. Conversely, water table position had only a weak influence on ER, but dominant contribution to ER switched from autotrophic respiration in wet years to heterotrophic in dry years. Droughts did not cause inter‐annual lag effects on ER in this rich fen, as has been observed in several nutrient‐poor peatlands. While ER was dependent on soil temperatures at 2 cm depth, FCH4 was linked to soil temperatures at 25 cm. Inter‐annual variability of deep soil temperatures was in turn dependent on wetness rather than air temperature, and higher FCH4 in flooded years was thus equally due to increased methane production at depth and decreased methane oxidation near the surface. Short‐term fluctuations in wetness caused significant lag effects on FCH4, but droughts caused no inter‐annual lag effects on FCH4. Our results show that frequency and severity of droughts and floods can have characteristic effects on the exchange of greenhouse gases, and emphasize the need to project future hydrological regimes in rich fens. We carried out a water table manipulation experiment at an Alaskan rich fen and monitored greenhouse gas exchange over 9 years to determine both short‐term and long‐term controls on methane emissions, ecosystem respiration, net ecosystem exchange and gross primary production. We explored lag effects and found that experimentally exacerbated droughts caused reduced gross primary production in subsequent wet years. We show that distinct hydrology and biogeochemistry of rich fens may cause them to respond characteristically to climate change.